Improving Verbal Linguistic Intelligence in Early Childhood Through the Use of Tiktok Media - Agus Nu'man; Indriana Rahmawati; Ahmad Zubaidi; Ainul Ainul; Hasti Retno Dewi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the increase in verbal-linguistic intelligence of early childhood through TikTok media at RA Al Husna Krejenengan Probolinggo. The research method used is a qualitative case study type. To get an idea of increasing verbal-linguistic intelligence of early childhood through the use of Tiktok media, researchers conducted interviews with school principals and teachers at RA Al Husna Krejenengan Probolinggo. The results showed that the Tik Tok application, together with appropriate methods and techniques, could be used as an interactive learning medium in increasing early childhood verbal-linguistic intelligence. With its various features and ease of operation, the Tik Tok application can be implemented in dialogue learning between teachers and students